1986
DOI: 10.1113/jphysiol.1986.sp016088
|View full text |Cite
|
Sign up to set email alerts
|

Comparative development of end‐plate currents in two muscles of Xenopus laevis.

Abstract: SUMMARY1. The development of miniature end-plate currents (m.e.p.c.s) was studied in the superior oblique and interhyoideus muscles of Xenopus laevis. An analysis of m.e.p.c. decays shows that each muscle possesses its own characteristic programme ofend-plate current development.2. In the superior oblique, the exponential decay constants of m.e.p.c.s were initially about 3 ms; they declined within half a day to 1 ms and remained at that value for six weeks. They then gradually became longer, reaching a mean va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…The recent discovery (Mishina et al, 1986) of a separate gene transcript encoding an adult form of the y-subunit of bovine AChR leaves little doubt that the 2 classes of AChR represent separate molecules, rather than different functional states of a single receptor type. Although the precise physiological significance for the existence of 2 types of AChRs is unknown, it is well-documented that the distribution and functional states of these 2 types of channels are not fixed but are labile and are altered during certain processes such as embryonic development (Fischbach and Schuetze, 1980;Michler and Sakmann, 1980;Brehm et al, 1984;Leonard et al, 1984;Siegelbaum et al, 1984) metamorphosis (Kullberg and Owens, 1986) innervation (Brenner and Sakmann, 1983), denervation (Allen and Albuquerque, 1986), or desensitization (Auerbach and Lingle, 1986;Igusa and Kidokoro, 1987).…”
mentioning
confidence: 99%
“…The recent discovery (Mishina et al, 1986) of a separate gene transcript encoding an adult form of the y-subunit of bovine AChR leaves little doubt that the 2 classes of AChR represent separate molecules, rather than different functional states of a single receptor type. Although the precise physiological significance for the existence of 2 types of AChRs is unknown, it is well-documented that the distribution and functional states of these 2 types of channels are not fixed but are labile and are altered during certain processes such as embryonic development (Fischbach and Schuetze, 1980;Michler and Sakmann, 1980;Brehm et al, 1984;Leonard et al, 1984;Siegelbaum et al, 1984) metamorphosis (Kullberg and Owens, 1986) innervation (Brenner and Sakmann, 1983), denervation (Allen and Albuquerque, 1986), or desensitization (Auerbach and Lingle, 1986;Igusa and Kidokoro, 1987).…”
mentioning
confidence: 99%
“…We interpret these results to mean that androgen-dependent activational changes in proteins mediating contraction are sufficient to generate the appropriate muscle mechanics needed for the clasping behavior and that significant remodeling of the synapse on a seasonal basis may be a costly procedure that would not be evolutionarily advantageous. We find these results to be interesting because previous studies have provided evidence suggesting that fiber contraction and synaptic properties are under coordinate regulation (Miledi and Uchitel, 1981;Fedorov et al, 1982;Kullberg and Owens, 1986;Henderson and Brehm, 1989). Our results suggest that in adult frogs, these two fundamental aspects of muscle function appear to be differentially susceptible to regulation by androgens.…”
Section: Discussionmentioning
confidence: 70%
“…Single fibers of the submaxillaris muscle exhibit both long branched end plates and small boutonlike contacts, which characterize fast twitch and slow tonic fibers, respectively (Miledi and Uchitel,198 1). Functional analysis indicates that intermediate fibers express a class of ACh receptor with open time kinetics lying between those of fast twitch and slow tonic fibers leading to the generation of synaptic currents of intermediate duration (Miledi and Uchitel, 1981;Fedorov et al, 1982;Kullberg and Owens, 1986). Prolongation of synaptic currents by cholinesterase inhibitors suggests that AChE activity in intermediate fibers is higher than in slow tonic and lower than in fast twitch fibers (Fedorov et al, 1982).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interhyoideus, a flat muscle of the lower jaw, begins to develop at about the same time. In other studies, we have shown that these muscles differ in their development of endplate currents and probably have 3 distinct patterns of AChR development (Kullberg et al, 1985;Kullberg and Owens, 1986).…”
Section: Methodsmentioning
confidence: 99%